Passionate Work? Labour Conditions in the Milan Fashion Industry. - Arvidsson, Adam; Malossi, Giannino; Naro, Serpica (Journal for Cultural Research, 2010)
This article analyses labour conditions among creative workers in the Milan fashion industry. Employing both qualitative and quantitative methods, the article shows how workers in the Milan fashion industry are generally underpaid and overworked. Despite such dire conditions, fashion work is generally considered gratifying and workers express high levels of satisfaction. The second part of the article attempts to unravel this paradox, departing from McRobbie's conception of passionate work. It suggests that the promotion of creativity as a desired form of life in the contemporary metropolis has shaped new forms of identity related to symbolic remuneration for work.